Choice for reinforced behavioral variability in children with autism spectrum disorder. Issue 3 (18th March 2020) - Galizio, Ann; Higbee, Thomas S.; Odum, Amy L.
Abstract : Although individuals with autism spectrum disorder (ASD) tend to behave repetitively, certain reinforcement contingencies (e.g., lag schedules) can be used to increase behavioral variability. In a lag schedule, reinforcers only follow responses that differ from recent responses. The present study was designed to promote variable play behavior in preschoolers with ASD interacting with playsets and figurines and to assess preference for variability and repetition contingencies. Data have shown a preference for variability in pigeons and college students, but this effect has not been explored in clinical populations. In this experiment, preschoolers with ASD were taught to discriminate between variability and repetition contingencies. Only play behaviors that met a lag schedule were reinforced in the presence of one color, and only repetitive behaviors were reinforced in the presence of another. After differential performance was established, participants experienced a concurrent chains schedule. Participants chose between the colors taught in training and then completed a play session with the selected contingency. One participant selected variability and repetition equally. The other participants showed a slight preference for variability. These results indicate that some individuals with ASD may play repetitively, not because they prefer repetition, but because they require additional teaching to play variably.